Regulation of Blood-Boosting Supplements for Anemia in Pregnant Women: Literature Review - Eni Widhiyaastuti; Arih Diyaning Intiasari; Suratman (Poltanesa, 2025)
Introduction: The number of pregnant women who suffer from anemia is 57.1% in Africa, 48.2% in Asia, 25.% in Europe, and 24.1 % in the US respectively. The 2021 Riskesdas shows that 78% of pregnant women experience anemia, up from 48.9% in 2019. Method: This research is a literature study using the PRISMA diagram approach, with article searches using the research databases Pubmed, Science Direct, Google Scholar, Sage Journal and Scopus from 2018-2024. The author formulated PICO to direct clinical searches, with the keywords "anemia", fe tablets" "pregnant women. The results of the search yielded 10 relevant articles related to the incidence of anemia in adolescents. Based on the results of a review of the article, it shows that anemia in pregnant women is caused by several factors, including socio-demographics, malnutrition and lack of intake of blood-boosting supplements. Conclusion: Providing blood-boosting supplements can prevent anemia in pregnant women which has an impact on the continuity of pregnancy and affects the fetus.